Topological Index of Coprima Graph of Integers Group Modulo with Order of Prime Power (Jurnal Matematika, Statistika dan Komputasi, 2025)
This paper explores the topological indices of the coprime graph defined on the group of integers modulo a prime power. A coprime graph is constructed with vertices representing group elements, where two vertices are adjacent if and only if their orders are relatively prime. The study focuses on analyzing four topological indices: the ABC index, Forgotten index, Gourava index, and Nirmala index. This work aims to enhance the understanding of the topological properties of coprime graphs within the structure of integer modulo groups of prime power order.
Keywords: ABC Index; Forgotten Index; Gourava Index; Nirmala Index; Coprime Graph